PERKEMBANGAN MANUSIA DALAM PANDANGAN PSIKOLOGI DAN AL-QUR’AN - Khotima, Husnul; Oktariani, Humairo; Aisyah, Neng; Harto, Kasinyo; Amilda, Amilda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The human creation of god has a perfect form in relation to his other creatures. Human development is essentially a fixed pattern with which each individual in general is a development that involves growth from the stage of conception down to the length of one's life span. The Koran contains several scriptures that show human development. Therefore the